Joyce in America : cultural politics and the trials of Ulysses - Segall, Jeffrey (University of California Press, 1993)
When James Joyce's Ulysses was first published in America, it quickly became a dynamic symbol of both modern art and the modern age. Jeffrey Segall skillfully demonstrates how various political, ideological, and religious allegiances influenced the critical reception and eventual canonization of what is perhaps the twentieth century's greatest novel. In re-creating the polemical debates that erupted, Segall provides a dramatic.